Perceived Safety and Fear of Crime of Visitors in a Shopping Mall in Karachi, Pakistan - Iqbal, Asifa (International criminal justice review, 2025)
This study examines the environment of one of the largest and most recently built shopping mall in Karachi, Pakistan. The aim of this study is to assess how building design, familiarity with the mall, and past experiences of victimization influence visitors’ perceived safety. Using site inspections guided by crime prevention through environmental design (CPTED) principles and an online survey, the study identifies factors affecting visitors’ perceived safety. Findings indicate that enhancing surveillance, territoriality, and access control in well-designed and maintained spaces can impact levels of perceived safety. These findings underscore the importance of surveys, in combination with site inspections, in providing a comprehensive tool for understanding and improving safety in commercial complexes.